(Dis)placement of Anthropological Legal Activism, Racial Justice and the Ejido Tila, Mexico. Issue 3 (24th August 2020) - Mora, Mariana
ABSTRACT: Through an analysis of a land‐dispute case involving indigenous Ch´ol community members in the state of Chiapas, Mexico, this article critically examines the role of anthropological knowledge in the production of the judicial arena as a terrain through which are disputed not only collective rights claims but also a sense of justice. The case of the Ch´ol ejido, or communal land holding, of Tila reached Mexico's Supreme Court in 2010. Yet five years later, tired of the excruciatingly slow pace of the judicial apparatus, Ch´ol ejido authorities rendered their own verdict by way of an assembly decision that reclaimed the 130 hectares under dispute as their own. This para‐state legal verdict unsettled the pre‐ascribed role of different political actors—the state judicial apparatus, human rights organizations, and anthropologists—whose interplay grants certain cohesion and sediment to the current judicial arena in the country when indigenous communities are implicated. The assembly decision and subsequent actions in the ejido Tila displaced these actors, including the Supreme Court judges, and in doing so rendered visible the racialized hierarchies that neither human rights organizations nor anthropologists were effectively able to subvert. [ legal activism, cultural expert witness reports, Indigenous territorial claims, racial justice, Latin America ] RESUMEN: A través de un análisis crítico de un caso de disputa de tierras que involucra un ejido indígena ch´ol en el estado de Chiapas, México, este artículo ofrece una aproximación crítica al papel que juega el conocimiento antropológico en la producción del campo jurídico como un terreno a través del cual se discute no sólo el acceso a los derechos colectivos sino el sentido de justicia. El caso del ejido Tila llega a la Suprema Corte de Justicia de la Nación en 2010, sin embargo, cinco años después y debido a la lentitud del aparato judicial las autoridades del ejido emiten su propia sentencia mediante una decisión de la asamblea de restituir las 130 hectáreas bajo disputa. Dicha sentencia legal para estatal desestabiliza los roles preasignados de diversos actores políticos –incluyendo los operadores de justicia, organizaciones de derechos humanos y los antropólogos– cuyas interacciones generan cierta cohesión y sedimento al campo judicial actual en México, particularmente en casos que involucran a pueblos y comunidades indígenas. La decisión de la asamblea y las acciones posteriores en el ejido Tila desplazan dichos actores, incluyendo los jueces de la Suprema Corte, lo que permite visibilizar las jerarquías racializadas que ni las organizaciones de derechos humanos, ni los antropólogos pudieron subvertir de manera efectiva. [ activismo legal, peritajes antropológicos, reclamos territoriales indígenas, justicia racial, Latinoamérica ]